Psychology : Selected Papers - Rossi, Gina; Rossi, Gina (IntechOpen, 2012)
This book represents a selection of chapters that address several topics from the broad domains of psychology: alcoholism, clinical interventions, treatment of depression, personality psychology, qualitative research methods in psychology, and social psychology. As such we have interesting blend of studies from experts from a diverse array of psychology fields. The selected chapters will take the reader on an exciting journey in the domains of psychology. We are sure the content will appeal to a great audience.
English
Keywords: Pharmacology; Medical toxicology